The Effect of Stress Distribution Around The Decline Shaft on The Support System Stability in Underground Mining - Pradani, Diana Irmawati (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2021)
The decline shaft is one of the main facilities in an underground mining work that is used as access to the mining panel from the surface. Making decline shafts on materials with weak characteristics is one of the important geotechnical issues that must be considered. The initial stage of making decline shaft holes is carried out on a relatively shallow ground surface or soil depth so that the horizontal stress that works is greater than the vertical stress. This excavation process will change the direction and magnitude of the initial stress from being in an equilibrium state to being disturbed. In addition to the stress on the rock mass, the condition of weak soil strength will affect the behavior and distribution of stresses working around the decline shaft hole. If the stress around the decline shaft exceeds the strength of the rock, there will be instability in the decline shaft so that strength is needed to control the existing stress.